DAMPAK KINERJA KEUANGAN TERHADAP RETURN SAHAM PERUSAHAAN KOSMETIK YANG TERDAFTAR DI BURSA EFEK INDONESIA - Wahyudi Wahyudi; Suriyanti Suriyanti (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2020)
This study aims to determine the Impact of CR, DER, and ROA on Stock Return. The research uses a theory/concept base, supported by previous studies which have similarities in variables. The object of this research is the Cosmetic Company which is listed on the Indonesia Stock Exchange. The type of data used is secondary data. Using descriptive statistical techniques and panel data regression assisted by Eviews 10.0 for data analysis. The results found that CR has a negative and significant effect on Stock Return, DER has a positive and not significant effect on Stock Return. ROA has a positive and not significant effect on Stock Return.